Pengaruh Pendapatan, Religiusitas, Jarak Lokasi, Tingkat Pendidikan dan Akses Informasi Terhadap Minat Masyarakat untuk Berwakaf Uang di Badan Wakaf Uang Tunai MUI DIY - Muhammad As Shadiqqy (LP2M UIN Sunan Kalijaga, 2019)
This study was conducted to examine the effect of income, religiosity, distance between site, education and access information to effect interest society in paying money cash wakf in Badan Wakaf Uang/Tunai MUI DIY. The population in this study were all society Daerah Istimewa Yogyakarta. The sample in this study were taken from most society with convinience sampling method. Determination of the number of samples using the formula slovin. There are 120 questionnaires that can be treated in this study. Primary data collection method used was survey method using a questionnaire media. In addition to the questionnaire, this research is also supported with the literature study and interview methods. Analysis of the data in this study using multiple probit regression analysis using EVIEWS shoftware 07.00 to test the research data.Regression analysis showed that of the four variables of income, religiosity, distance between site, education and access information of test results obtained simultan probability level of significance of 0.000 ≤ 0.05. It can be concluded that the regression model can be used and jointly affect the interest society in paying money cash wakf. To test z can be concluded that religiosity significant positive effect on society interest in paying money cash wakf. While the income, distance between site, education and access information does not affect the interest society in paying money cash wakf.Based on test results obtained McFadden determination coefficient R2 of 0.824. It can be concluded that society interest in paying money cash wakf in Badan Wakaf Uang/Tunai MUI DIY able to be explained by the independent variables which include income, religiosity, distance between site, education and access information that is equal to 82.4% and the rest is explained by other variables outside the research model that is equal to 0.176 (17.6%).